Clinical epidemiological characterization of suspicious and positive patients to the COVID-19 in an isolation center from Santiago de Cuba - Laidelbis Minier Pouyou; Arístides Ramón Rodríguez Julian; Mayelin Marin Méndez; Yayma Fuentes Gómez (Centro Provincial de Información de Ciencias Médicas, 2021)
Introduction: Cuban science has offered significant contributions for the confrontation to the COVID-19, what has facilitated, by means of diverse investigations, the prediction, design of confrontation ways, as well as the improvement of therapeutic protocols and performance models.   Objective: To characterize suspicious and positive patients to the COVID-19 admitted to an isolation center from Santiago de Cuba.  Methods: An observational, descriptive and cross-sectional study of the 731 suspicious and positive patients to the COVID-19 was carried out. They were admitted to the Medicine Faculty No. 2 isolation hospital from Santiago de Cuba, from January to March, 2021, aimed at characterizing them according to some selected clinical and epidemiologic variables, that is: age, sex, personal pathological history and symptoms at the moment of the diagnosis.  Results: Of the total of patients there was a prevalence of the male sex (50.8 %) and the 21-30 and 51-60 age groups (21.6 and 20.7 %, respectively). In connection with the number of confirmed cases there was a prevalence of females (29.2 %) and the health areas with more affected patients were  28 de Septiembre (22.5 %), 30 de noviembre (16.8 %) and Mario Muñoz Monroy polyclinics (14.6 %); also,  hypertension, bronchial asthma and other allergies are notable as personal pathological history, besides  cough,  fever and  diffuse discomfort as clinical signs. It is remarkable that 45.6 % of the patients with positive test were asymptomatic at the moment of the diagnosis.  Conclusiones: The COVID-19 constitute a high-priority problem of public health and the confrontation to this terrible pandemic not only  has brought in itself to postpone goals and  transform objectives of life in all  sectors and nations, but it has also implied to constantly redefine strategies and ways of doing in the search of a better control of the disease.